Understanding The Strategies Employed by EFL Learners to Overcome Speaking Anxiety in The Classroom - Veronika Simbolon (MIREJ: Multidisciplinary Innovation Research Journal, 2025)
This research study aims to investigate the strategies employed by English as a Foreign Language (EFL) learners to overcome speaking anxiety in the classroom. Speaking anxiety is a significant challenge faced by EFL learners, hindering their development of fluency and confidence in speaking. However, there is limited understanding of the specific strategies used by EFL learners to cope with and overcome this anxiety in the classroom context. This study adopts a qualitative research design, utilizing interviews and observations to gather in-depth data from EFL learners. The findings reveal a range of strategies employed by participants, including cognitive strategies (positive self-talk, visualization, and reframing anxious thoughts), preparation and practice, a supportive learning environment, gradual exposure and desensitization, and emotional regulation techniques. These strategies contribute to the effective management of speaking anxiety and the promotion of speaking proficiency among EFL learners. The insights from this study provide valuable implications for educators and practitioners, enabling the development of targeted interventions and instructional approaches to support EFL learners in managing their anxiety and enhancing their speaking skills. By addressing speaking anxiety effectively, language teaching and learning practices in the EFL context can be improved, fostering a positive and inclusive environment for EFL learners to develop their speaking abilities with confidence.